Comprehensive recycling of fresh municipal sewage sludge to fertilize garden plants and achieve low carbon emission: A pilot study - Lin, Xianke; Chen, Canming; Li, Huashou; Hei, Liang; Zeng, Luping; Wei, Zebin; Chen, Yangmei; Wu, Qi-Tang (Frontiers in Environmental Science, 2022)
Recycling nutrients in municipal sewage sludge (MSS) to soil would support sustainable development. In this study, a comprehensive recycling using specific plants able to grow in the fresh MSS and an indirect application technique was developed. Fresh MSS was placed in permeable containers next to Handroanthus chrysanthus plants to provide indirect fertilization. Sludge treatment plants (Alocasia macrorrhiza and Pennisetum hybridum) were grown directly on the Fresh MSS to produce plant biomass and treat MSS. The basal diameters of the H. chrysanthus plants were markedly increased by the treatment. Nutrients were extracted from MSS more readily and more biomass was produced by the P. hybridum than the A. macrorrhiza plants. The heavy metal contents of the soil did not increase significantly and not generate potential ecological risk, but the organic matter, nitrogen, and phosphorus contents increased markedly. The fresh MSS leachate met the relevant fecal coliform and heavy metal irrigation water standards. At the end of the treatment, the MSS mass had markedly decreased and the treated MSS was used as a seedling substrate for two garden plant seedlings. The net carbon emissions from the comprehensive recycling are estimated as -15.79 kg CO2e (CO2 equivalent) per ton fresh sludge, in contrast, the emissions from composting treatment are estimated as 8.15 kg CO2e. The method allows nutrients in MSS to be recycled without causing heavy metal pollution and without net carbon emission, while gives gardening products with commercial value.